1995
DOI: 10.5694/j.1326-5377.1995.tb139937.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and predictors of outcome in an Australian cohort with hepatitis C virus infection

Abstract: Objectives: To define demographic and epidemiological features of an Australian population with chronic hepatitis C virus (HCV) infection and determine predictors of histological and clinical outcome. Design: Cohort study. Patients and setting: 342 consecutive HCV antibody‐positive patients referred to the liver clinic of a major metropolitan general hospital. Outcome measures: Demographic data, serial alanine aminotransferase (ALT) levels, full blood count for all patients. Percutaneous liver biopsy in 152 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 25 publications
3
21
3
Order By: Relevance
“…Cirrhosis was diagnosed in 18% of our group who underwent liver biopsy. This is significantly lower than the 32% found in the report by Strasser et al 14 The present larger population sample is likely to be more representative of the HCV community in Australia; however, there is still likely to be some referral bias in this clinic population. Other investigators have reported cirrhosis in 18–21% of their subjects 7,19 .…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Cirrhosis was diagnosed in 18% of our group who underwent liver biopsy. This is significantly lower than the 32% found in the report by Strasser et al 14 The present larger population sample is likely to be more representative of the HCV community in Australia; however, there is still likely to be some referral bias in this clinic population. Other investigators have reported cirrhosis in 18–21% of their subjects 7,19 .…”
Section: Discussioncontrasting
confidence: 66%
“…A history of IDU was present in 64% of patients, compared with 51% in the previous report 14 . Furthermore, over two‐thirds (68%) of HCV patients seen in our clinics over the last 4 years have been IDU.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition to Farrell and the Westmead group Paul Desmond has made substantial contributions in this area as well as in viral hepatitis. His research has centered around (i) Drug metabolism in liver disease particularly the relative preservation of glucuronosyl‐transferase enzymes in comparison with Cytochrome P450 (this followed working with Dr. Stephen Schenker in Nashville, USA); 46 (ii) hepatitis C around clinical outcomes based on a large database of patients seen over 18 years at St Vincents and collaboration with Stephen Locarnini in basic research 47 and clinical trials; 48 (iii) hepatitis B clinical and basic research particularly in collaboration with Locarnini; and (iv) clinical research into biliary disease particularly the definitive study on accuracy of MRCP.…”
Section: Hepatic Drug Metabolismmentioning
confidence: 99%